KOMPARASI KEARIFAN LOKAL SUNDA DAN JEPANG: PEMBENTUK KARAKTER ANAK - Nani Sunarni (Badan Pengembangan dan Pembinaan Bahasa, 2017)
In the current era of globalization, cultures blend and dominate each other, making children confuse about their identity. Indonesia, as a multiracial and multicultural nation, is very rich in local wisdoms, and this wealth can be applied to build the character of children and fortify themselves from the negative influence of global or foreign cultures. Japan is a nation that lives based on culture and use local wisdoms as a foundation of life and learning materials that are directly implemented in everyday life. The same thing can be seen in the Sundanese society. Today many children do not recognize their own local wisdoms. This, according to the researchers, is due to the vacuum of local wisdom values in the curriculum and learning process. Therefore, various researchs on local wisdoms learning need to be done, include the learning program through oral tradition such as pupuh and folktale, and also traditional game. The method used in this research is descriptive qualitative method. The data used is the local wisdoms learning in Sundanese culture, which is the learning schedule related to local wisdoms that is limited to character building, and data related to local wisdoms in education in Japan, which is the schedule of